A configuração do Sistema Nacional de Repressão no governo JK (1956 a 1961) - Oliveira, Nilo Dias de (2013)
This thesis presents the structure of Brazil`s Intelligence Service, also known as the National Security System, which from the second half of the 1950s to the height of the Juscelino Kubitschek government (1956-1961) acquired the stature and complexity that enabled it to provide surveillance and control of the entirety of Brazilian society. Interconnection of the principal agencies acting as police security systems, namely the National Security Council (CSN), the Social Policy Division of Police (DPS), the National Security sections existing in all Civil Ministries of the Republic, as well as Information Services of Police of Political and Social Order (DOPS) and the Secretaries of State Security comprised for the first time in Brazil a complex system integrated both horizontally and vertically throughout the repressive apparatus of the state. Being structured as a "single central national information," its ramifications also extended internationally through connections with the Police security systems in several European countries, North America and Latin America. In developing this thesis we used documents from the National Security Council largely located in the National Archives of Brasilia, and CPDOC, the Getulio Vargas Foundation in Rio de Janeiro. Thus existing documents from the collections of the CPDOC depository of the personal archives of General Tavora and military officer and politician Congressman and Governor Ernani do Amaral Peixoto were necessary; documents from the Bureau of Political and Social Order of São Paulo SP-DOPS, located in the Public Archives of the State of São Paulo; and documents from the Division of Police and Social Policy DPS, the Public Archives of the State of Rio de Janeiro. According to guidelines for the fight against communism, promulgated under the aegis of the Cold War and espoused in Latin America by the United States, these actions allowed the more conservative and dominant segment to remain in permanent conflict with civil society concerning recommended alternatives for Brazil s economic development in order to consolidate its power. Even to the extent of coordination with the Armed Forces. Also participating at the time of these military clashes, with loud disapproval, proposing alternatives to national development and which were collected by storm for many of the purges engineered by security organs at the time, were those arbitrarily accused as communists or sympathizers. Coincidentally, it was the military that gave support to maintaining of democratic openness. On the other hand, the most diverse sectors of society eager for freedom on constitutional grounds began to express themselves through repeated discussions, demonstrations, strikes, etc., in work demands, political opinions or on public affairs in general as well as on international issues at that moment. However, beneath an apparent climate of democracy at the end of the 1950s there was a nearly total control thrived that could be mapped with increasing detail of the greater part of the demonstrations in Brazil. Thus it became necessary to integrate the Brazilian Armed Forces responsible for implementing the National Security Doctrine (DSN), with Civil and Military Police throughout the country. Directly subordinate to the National Security Council (NSC), such a system, which began at that time, could provide information to the central authorities of the Government about any individual or existing organization. It could even define who or what should be observed, or violently repressed, or restricted in their freedoms and public activities